Analisis Perlindungan Hak Tanah Ulayat Masyarakat Adat Suku Dalam (Terasing) dalam Perspektif Hak Asasi Manusia - Muhammad Nur Karim Al Ismariy; Lailasari Ekaningsih; Ridho Saadillah Ahmad (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2026)
The marginalization experienced by the Suku Dalam (indigenous and isolated community) reflects the persistent weakness of human rights protection for indigenous peoples, particularly in ensuring the right to a decent standard of living through control over customary land (tanah ulayat). Customary land is not merely an economic asset, but constitutes a living space, cultural identity, and the foundation of social and ecological sustainability for the Suku Dalam. This study aims to analyze the forms of human rights protection afforded to the Suku Dalam in relation to the right to a decent life, to examine the legal status and recognition of customary land within the national legal system, and to assess the role and responsibility of the state in guaranteeing the protection of indigenous peoples’ rights. This research employs a normative juridical method with statutory and conceptual approaches, based on library research of legislation, court decisions, and national as well as international human rights instruments. The findings indicate that although the legal recognition of indigenous peoples and customary land exists normatively, its implementation remains weak due to overlapping regulations, limited participatory mechanisms, and the dominance of economic development interests. Therefore, the state is required to strengthen substantive protection through affirmative policies, recognition of customary territories, and consistent application of human rights principles to ensure a dignified and decent life for the Suku Dalam. Keywords: Suku Dalam, Human Rights, Customary Land, Decent Living, Indigenous Peoples.